Facilitators and Barriers to Antiretroviral Therapy Adherence Among Adolescents and Young Adults in Sub-Saharan Africa: A Scoping Review - Enos Moyo; Perseverance Moyo; Hadrian Mangwana; Grant Murewanhema; Tafadzwa Dzinamarira (Adolescents)
Background: Globally, approximately 65% of adolescents undergoing antiretroviral therapy (ART) adhered to their treatment, whereas only 55% achieved viral suppression in 2023. The low rate of viral suppression is concerning, as elevated viral loads are associated with a heightened risk of opportunistic infections, progression to advanced HIV disease, increased mortality, and greater HIV transmission rates. We conducted this scoping review to identify the facilitators and barriers to ART adherence among adolescents and young adults (AYAs) in sub-Saharan Africa (SSA). Methods: We conducted this scoping review following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) checklist. We searched for peer-reviewed articles published in English from 2014 to 2024 across the SCOPUS, ScienceDirect, PubMed, Africa Journals Online, and Google Scholar databases. Two reviewers independently selected the articles and extracted the data. We used NVivo to develop codes and categories of facilitators and barriers. Results: We used 30 articles reporting on studies conducted in 13 countries in this review. The total number of participants in the studies was 12,250. Sixteen articles reported on qualitative studies, nine on quantitative studies, and five on mixed-methods studies. This scoping review identified various personal (14 articles), interpersonal and social (15 articles), healthcare system-related (9 articles), medication-related (7 articles), and economic (2 articles) factors that facilitate ART adherence among AYAs. Additionally, the scoping review also identified various personal (28 articles), interpersonal and social (13 articles), healthcare system-related (14 articles), medication-related (20 articles), school- or work-related (6 articles), and economic (14 articles) factors that hinder ART adherence among AYAs. Conclusions: Enhancing ART adherence in AYAs requires multiple strategies, including the reduction of internalized stigma, implementation of community awareness campaigns, harm reduction approaches for AYAs who misuse substances, comprehensive education on HIV, and the provision of support from school staff and leadership, alongside the adoption of differentiated service delivery (DSD), which encompasses home-based ART delivery, refills at private pharmacies, community ART distribution centers, and patient-led community ART refill groups, as well as multi-month dispensing practices.